Cultural and artistic mediation in libraries: structures in process of construction - Rasteli, Alessandro [UNESP]; Formentini Caldas, Rosangela [UNESP] (Collegi Oficial Bibliotecaris & Documentalistes Comunitat Valenci, 2018)
The report reflects about the concepts of cultural mediation and artistic mediation in libraries. The research has a theoretical orientation, because it tries to clarify questions by examining the themes in the literature, identifying and consulting bibliographic materials, as well as raising appropriate aspects for cultural mediation and artistic mediation in order to make the concepts explicited. From this perspective, the libraries, as spaces of culture and arts, or similar themes, is a line of research still underdeveloped in Information Science in the context of Brazil. The notion of cultural and artistic mediation in libraries works in order to promoter actions for the access, production and appropriation of cultural and artistic elements, inserting the community into practices that will result in the social and cultural development.
Keywords: Cultural mediation; Artistic mediation; Cultural appropriation; Cultural action